Alternative Income Tax Incentives in Islamic Banks and Theory - Rifky, Muhammad; Rokan, Mustafa Kamal; Sugianto; Rizal, Muhammad; Rizki, Oktavera (International Journal of Accounting and Economics Studies, 2025)
Islamic bank financing has a greater influence on the economy compared to conventional bank credit. The ability to generate profits is inferior to that of conventional banks. To increase financing with the Profit Loss Sharing (PLS) scheme, Islamic banks need to be careful because of the high risk. Therefore, Income Tax incentives are needed for Islamic banks to increase financing with the PLS scheme. This Income Tax incentive will reduce the Income Tax burden and add capital to increase financing. By using grounded theory, two Income Tax incentive schemes can be obtained from financing with the PLS scheme, namely profit sharing from profit after Income Tax, which is like dividends, and income from financing, like venture capital companies. The most applicable scheme is financing from venture capital companies. The purpose of this Income Tax Incentive is supported by growth theory. In its application, it is supported by knowledge-based theory. To achieve the expected goals, the concept of stakeholder theory must be considered. To ensure that the tax authority is willing to make further regulations for its implementation, further study is needed regarding how much and how long Income Tax revenues are reduced from this incentive.